Molecular characterization of mutations in white-flowered torenia plants - Nishihara, Masahiro (BMC Plant Biol, 2014)
BACKGROUND: Torenia (Torenia fournieri Lind.) is a model plant increasingly exploited in studies in various disciplines, including plant engineering, biochemistry, physiology, and ecology. Additionally, cultivars with different flower colors have been bred and made commercially available. Flower color in torenia is mainly attributed to the accumulation of anthocyanins, but the molecular mechanisms inducing flower color mutations in torenia have not been well elucidated. In this study, we therefore attempted to identify the cause of white coloration in torenia by comparing the white-flowered cultivar Crown White (CrW) with Crown Violet (CrV), a violet-flowered variety. RESULTS: In an expression analysis, no flavanone 3-hydroxylase (TfF3H) transcript accumulation was detected in CrW petals. Sequence analyses revealed that a novel long terminal repeat (LTR)-type retrotransposable element, designated as TORE1 (Torenia retrotransposon 1), is inserted into the 5′-upstream region of the TfF3H gene in CrW. A transient expression assay using torenia F3H promoters with or without TORE1 insertion showed that the TORE1 insertion substantially suppressed F3H promoter activity, suggesting that this insertion is responsible for the absence of F3H transcripts in white petals. Furthermore, a transformation experiment demonstrated that the introduction of a foreign gentian F3H cDNA, GtF3H, into CrW was able to recover pink-flower pigmentation, indicating that F3H deficiency is indeed the cause of the colorless flower phenotype in CrW. Detailed sequence analysis also identified deletion mutations in flavonoid 3′-hydroxylase (TfF3′H) and flavonoid 3′,5′- hydroxylase (TfF3′5′H) genes, but these were not directly responsible for white coloration in this cultivar. CONCLUSIONS: Taken together, a novel retrotransposable element, TORE1, inserted into the F3H 5′-upstream region is the cause of deficient F3H transcripts in white-flowered torenia, thereby leading to reduced petal anthocyanin levels. This is the first report of a retrotransposable element involved in flower color mutation in the genus Torenia.